2000
DOI: 10.1111/1467-9663.00124
|View full text |Cite
|
Sign up to set email alerts
|

Border Crossings: Small Enterpreneurs and Cross‐border Trade between South Africa and Mozambique

Abstract: Based on research conducted in 1999/2000, this paper examines the vibrant informal sector cross-border trade between South Africa and Mozambique. It provides an overview of the small and medium entrepreneurs involved in this trade as well as the kinds and volumes of goods that they carry across the border. It suggests that the use of the term 'informal' to describe this trade may be misleading as it obscures the multiple linkages between the formal and informal sectors in both countries. Furthermore, it implie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 11 publications
(16 reference statements)
5
45
0
Order By: Relevance
“…The overall analysis of how informal traders overcome the constraints they faced suggested the following coping mechanisms, (i) give bribe, (ii) act collectively when facing problem, and mainly female traders often adopted such a strategy, and (iii) others such as the use of children with rickshaws, use of stuntmen motorcyclists to by-pass the different crossing points, or even resort to prostitution. These results corroborate with those related on East and Southern Africa countries (Peberby, 2000a, 2000b, 2000cand Masheti, 2009). The previous results have important implications in terms of economic, trade, and sectoral policies formulation for wealth creation and poverty alleviation.…”
Section: Resultssupporting
confidence: 90%
“…The overall analysis of how informal traders overcome the constraints they faced suggested the following coping mechanisms, (i) give bribe, (ii) act collectively when facing problem, and mainly female traders often adopted such a strategy, and (iii) others such as the use of children with rickshaws, use of stuntmen motorcyclists to by-pass the different crossing points, or even resort to prostitution. These results corroborate with those related on East and Southern Africa countries (Peberby, 2000a, 2000b, 2000cand Masheti, 2009). The previous results have important implications in terms of economic, trade, and sectoral policies formulation for wealth creation and poverty alleviation.…”
Section: Resultssupporting
confidence: 90%
“…As demonstrated by a number of independent research investigations as well as a cluster of work linked to the Southern African Migration Project this form of informal business tourism is widespread between South Africa and other countries in southern Africa, most importantly Lesotho, Swaziland, Mozambique, Zimbabwe and Malawi (Muzvidziwa, 1998;Peberdy & Crush, 1998;Peberdy, 2000aPeberdy, , 2000bPeberdy & Crush, 2001;Peberdy & Rogerson, 2003;SBP, 2006;ComMark Trust, 2008;International Organization for Migration, 2010;Muzvidziwa, 2010;Chiliya, Masocha & Zindiye, 2012;Jamela, 2013). Johannesburg is host to a large circulating community of informal business travellers, mostly informal traders who cross South Africa's borders on a temporary basis to trade, shop and buy-and sell (Crush, 2005;Rogerson, 2011;Jamela, 2013).…”
Section: Conceptualizing Business Tourism In Africamentioning
confidence: 99%
“…Works by Peberdy and Crush (1998) and by Peberdy (2000aPeberdy ( , 2000bPeberdy ( , 2007 confirm that women entrepreneurs are most likely to be engaged in the more mobile segments of cross-border trade and selling, among other items, groceries, fresh food, clothing and craft goods. It is shown that communities of women traders operating in South Africa 'often travel to sell for only one week per month, and many sell direct to shops and customers and are more likely to be involved in cross-border "shopping" ' (Peberdy & Rogerson, 2000, p. 31).…”
Section: Informal Sector Business Tourism and Pro-poor Tourismmentioning
confidence: 99%
“…McGregor (1998) has shown that what began as survival strategies have now become key elements of identity formation in some African cross-border regions. Similarly, Peberdy (2000) has contended that cross-border informal trade is a means to protest against weak state protection at the national level. Thus, she argues that what occurs in borderlands reflects weak governance at the center.…”
mentioning
confidence: 99%